Statistical Analysis of the Hydrological and Hydrometeorological Characteristics of the Upper Tisza Basin - Czomba, Péter; Vass, Róbert; Túri, Zoltán Krisztián (Journal of Environmental Geography, 2023)
Tisza is the largest water base in the eastern part of Szabolcs-Szatmár-Bereg County, in north-eastern Hungary, and its indirect use is mainly associated with agriculture. Our work investigates the hypothesis that decrease in water levels and water discharges of the Upper Tisza in recent decades, together with the incision of the riverbed and the precipitation falling in the area, have an impact on the groundwater level of the Szatmár-Bereg Plain. In our study, data from three water gauges located between the settlements of Tiszaújlak and Vásárosnamény and data from groundwater level monitoring wells (MW) and Hydrometeorological (HMS) stations on the Szatmár-Bereg Plain were compared using statistical methods in Past 4.11 software. The aim of the current study was to identify the strategic steps that need to be taken by the organisations responsible for water management in the Upper Tisza basin in the light of the changes in hydrological, hydrometeorological, and meteorological factors. To ensure that the region has sufficient water supplies for the next decade, appropriate water management and agricultural strategies could be the solution.